Mt. Fuji in the Ocean–Description of a Strange New Species of Sea Anemone, Discoactis tritentaculata fam., gen., and sp. nov. (Cnidaria; Anthozoa; Actiniaria; Actinostoloidea) from Japan, with the Foundation of a New Family and Genus - Takato Izumi; Kensuke Yanagi; Hisanori Kohtsuka (Diversity)
A new species in a new family and genus of sea anemone, Discoactis tritentaculata fam. gen. and sp. nov., was discovered at several localities around Japan. These anemones were indicated to belong to the superfamily Actinostoloidea by phylogenetic analyses. However, the specimens have flat, disc-like bodies; triplet tentacles on the oral disc; endocoels without tentacles; 10 macrocnemes in the column; and numerous microcnemes only in the aboral end. These features are unique among not only Actinostoloidea but also sea anemones in general, and thus they could not be accommodated into any existing families and genera in Actinostoloidea. Therefore, we establish the new family Discoactinidae and the new genus Discoactis for this species of anemone. Our phylogenetic analyses also suggested that the family Capneidae, of which the phylogenetic position has not been certainly convinced yet, also should be a member of Actinostoloidea, and thus we revised its placement and discussed the diagnosis of the superfamily. With these results, the superfamily Actinostoloidea now accommodates eight families.